Combining a McGrath Video Laryngoscope and C-MAC Video Stylet for the Endotracheal Intubation of a Patient with a Laryngeal Carcinoma Arising from the Anterior Side of the Epiglottis: A Case Report - Richard L. Witkam; Jörgen Bruhn; Nico Hoogerwerf; Rebecca M. Koch; Lucas T. van Eijk (Anesthesia Research)
Introduction: Difficult airway management is a critical challenge in anesthesia, often necessitating advanced techniques to ensure patient safety. A patient presented with a malignant lesion on the epiglottis, significantly altering the airway anatomy. Flexible rhinolaryngoscopy revealed a laryngeal carcinoma affecting the entire epiglottis, causing thickening and displacement, which suggested the potential for difficult intubation. Methods: Given the expected feasibility of bag-mask ventilation and front-of-neck access, an asleep intubation technique was selected. The combined use of a McGrath video laryngoscope and C-MAC video stylet allowed for fast and easy atraumatic intubation on the first attempt. The anesthetic and surgical course was uneventful. Discussion: This case report highlights the successful use of a combined approach involving a video laryngoscope and video stylet for intubation in a patient with known difficulties in airway management, providing insights into the benefits of enhanced visualization and maneuverability. The rigid design and steerable tip of the C-MAC video stylet provide advantages over traditional flexible optics, offering better maneuverability and reducing the need for a second operator. Although this technique was successful in this case, its use in patients with complex airway pathologies warrants careful preoperative assessment and collaboration with an experienced airway management team.